Description of a new species of crested newt, previously subsumed in Triturus ivanbureschi (Amphibia: Caudata: Salamandridae) - Wielstra, B.; Arntzen, J.w. (Zootaxa, 2016)
Multilocus molecular data play a pivotal role in diagnosing cryptic species (i.e. genetically distinct but morphologically similar species). A multilocus phylogeographic survey has provided compelling evidence that Triturus ivanbureschi sensu lato comprises two distinct gene pools with restricted gene flow. We conclude that this taxon had better be treated as two distinct (albeit morphologically cryptic) species. The name T. ivanbureschi should be restricted to the western species, which is distributed in western Asiatic Turkey plus the south-eastern Balkan Peninsula. No name is as yet available for the eastern species, which is distributed in northern Asiatic Turkey. We propose the name T. anatolicus sp. nov. for the eastern species and provide a formal species description.